Russula fanjing, a new species of Russula subsect. Russula (Russulaceae, Russulales) from Guizhou province, China - Li, Fang; Li, Guo-Jie; Zhang, Jing; Gao, Huan; Shi, Ru-Shu; Deng, Chun-Ying (Phytotaxa, 2021)
Russula fanjing is proposed here as a new species based on morphological and molecular evidence. The new species is described and illustrated with photographs and line drawings and compared to related species. Morphologically, R. fanjing (subgenus Russula, section Russula, subsection Russula) is characterized by a medium-sized basidioma, with a vivid red to pastel red areolate pileus, white lamellae occasionally forked near the stipe with lamellulae, a smooth white stipe, basidiospores ornamented with strongly amyloid warts and ridges interconnected by fine lines in an incomplete or complete reticulum, and a pileipellis a typical trichoderm with suprapellis cells composed of short-celled, claw-like branched, lotus-root-like inflated hyphae and dispersed clavate, septate pileocystidia. The phylogenetic analysis of the nucleotide sequences of the internal transcribed spacer (ITS) region provided further evidence that the described species belongs to subsection Russula and represents a new taxon.